P335Sudden unexplained death in Catalonia: comprehensive genetic analysis in post-mortem samples. (15th July 2014) - Sanchez-Molero, OE; Campuzano, O; Allegue, C; Selga, E; Mademont, I; Coll, M; Mates, J; Iglesias, A; Medallo, J; Brugada, R
Abstract: Purpose: Cardiovascular pathologies are the main cause of sudden death in developed countries. In population older than 50 years old, most deaths are due to coronary disease alterations, in the young deaths may be caused by "monogenetic disorders", channelopathies, or cardiomyopathies. Genetic analysis is not routinely performed in autopsy protocol when a cause of death is not identified in the young. In recent years the development of next generation sequencing (NGS) technology allows the investigation of high number of genes in a short period of time at low cost. We launched the MOSCAT project, a prospective post-mortem study that aims to identify the genetic cause of death in cases that remains without a conclusive diagnosis after a complete autopsy. Methods: Our cohort included a total of 88 cases: <50 years old, and no-conclusive cause of death after complete autopsy investigation. We divided the cohort into two groups, depending on DNA quality for NGS analysis. The first group included 59 samples with low quality. The main seven arrhythmogenic genes (KCNQ1, KCNH2, KCNE1, KCNE2, KCNE3, RYR2 and SCN5A) were analyzed using Sanger method. The second group included 43 samples analyzed by NGS, a total of 55 genes associated with SCD were analyzed. Potentially pathogenic role was determined when minor allele frequency (MAF) was less than 1% and at least one in silico prediction. A total of 14 samples were analyzed using both methods as internal control. Results: Our cohort of 88 samples showed a gender ratio of 2:1 (men: women respectively). In group 1 (sanger, 59 samples) we identified 30% arrythmogenic mutation carriers. In group 2 (NGS, 43 samples) we identified 15% arrythmogenic mutations and 85% associated with structural cardiomyopathies. Acording to age in group 1 we identified 27% mutations in patients younger than 35 and 34% in older than 35. By NGS we identified 50% arrythmogenic mutations and 50% structural mutations in less than 35 and 40% arrythmogenic mutations and 60% structural mutations in older than 35. Conclusions: In patients younger than 50, we identified arrythmogenic mutations in 25% and structural mutations in 70% of cases studied. Nearly 30% of post-mortem cases minor than 50 years with a no-conclusive cause of death carry a potential pathogenic variation that could explain the death. NGS technology adds additional information and may be useful in the identification of genetic causality. We believe that genetic analysis should be included in routine forensic guidelines when a no-conclusive cause of death arises, especially in cases under 35 years old.